Guidelines for Systematic Fault Tolerance Requirements Extraction in Systems-of-Systems from Business Process-of-Processes - Molina, Sidny Almeida; Paiva, Débora Maria Barroso; Cagnin, Maria Istela (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information Systems, 2025)
This paper presents a set of guidelines for the systematic extraction and specification of fault tolerance requirements in Systems-of-Systems (SoS) based on Processes-of-Business Processes (PoP) models in BPMN. The extracted requirements aim to reach reliability during the SoS interoperability, which automate the corresponding PoP, and the alignment between the technical and business levels. The guidelines were evaluated through a study case. The results indicate that the guidelines support the systematic extraction of fault tolerance requirements from essential information of the business level.